1969
DOI: 10.1017/s0022029900012620
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid and tocopherol levels in the serum of apparently healthy dairy cattle

Abstract: Total carotenoids, β-carotene and α-tocopherol concentrations were determined in serum from healthy dairy cattle of various ages, grazing good quality pasture, in different areas of New South Wales. The relationships of these components with each other and with age of the animal were examined.Mean serum β-carotene concentrations for heifers and cows were 0·68 and 1·20mg/100ml, respectively. These concentrations were somewhat higher than those found for calves (0·20mg/100ml) and weaners (0·37 mg/100 ml). Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Differences (P<.05) were significant only between seasons and ranches with levels higher in the wet season. Bayfield and Mylrea (1969) reported that serum vitamin E concentrations increased from 2.20 mg/100 ml in calves to 3.70 mg/100 ml in weanlings, while heifers and cows had levels between 5.40 and 9.00 rag/100 ml.…”
Section: Calcium Phosphorus and Magnesium Tissuementioning
confidence: 99%
“…Differences (P<.05) were significant only between seasons and ranches with levels higher in the wet season. Bayfield and Mylrea (1969) reported that serum vitamin E concentrations increased from 2.20 mg/100 ml in calves to 3.70 mg/100 ml in weanlings, while heifers and cows had levels between 5.40 and 9.00 rag/100 ml.…”
Section: Calcium Phosphorus and Magnesium Tissuementioning
confidence: 99%
“…3 Canadian researchers testing 10 clinically normal cows from 5 different herds found mean serum vitamin E concentrations in the 5 herds to range from 2.19-5.3 mg/ml. 8 Another author estimated that serum vitamin E concentrations from 0.8-1.2 mg/ml should be the reference range for cattle.…”
mentioning
confidence: 99%
“…Serum α-tocopherol concentrations of 1.0–1.5 μg/ml were associated with NMD in Irish cattle, 14 and values <2 μg/ml were considered deficient 14 . Serum α-tocopherol concentrations >4.0 μg/ml have been reported to be adequate in adult dairy cattle 3 . Canadian researchers testing 10 clinically normal cows from 5 different herds found mean serum vitamin E concentrations in the 5 herds to range from 2.19–5.3 μg/ml 8 .…”
mentioning
confidence: 99%
“…According to the concentration of α-tocopherol in plasma, the subclinical VE deficiency group (2-3 µg/ml α-tocopherol) and the healthy control group (>4 µg/ml α-tocopherol) were determined (10)(11)(12). Finally, after excluding all other cases of perinatal disease, 67 cows were selected as test animals.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…This process makes early post-partum cows prone to subclinical VE deficiency and systemic oxidative stress. Plasma concentrations of α-tocopherol in cows at 2-3 µg/ml can be identified as subclinical VE deficiency (10)(11)(12). Vitamin E deficiency and oxidative stress are important causes of perinatal dairy cows' susceptibility to productive diseases (13).…”
Section: Introductionmentioning
confidence: 99%